2019
DOI: 10.1097/shk.0000000000001477
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and Adverse Effects of Thrombomodulin Alfa to Treat Sepsis-Induced Disseminated Intravascular Coagulation

Abstract: In the treatment of disseminated intravascular coagulation (DIC), which is a complication of underlying diseases such as infections and malignant tumors, effective plasma concentrations of thrombomodulin (TM) alfa range from 300 to 900 ng/mL; however, appropriate concentrations when treating sepsis-induced DIC are unknown. Thus, our aim was to determine the relationship between plasma concentrations of TM alfa and its therapeutic effects, and hemorrhagic adverse events. First, we calculated the plasma trough c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Renal replacement therapy was performed in 55 patients (53.9%). The median (interquartile range) SOFA score was 11 (9)(10)(11)(12)(13)(14), the median (interquartile range) JAAM-DIC score was 6 (5-7), and the median (interquartile range) SIRS criterion was 3 (2-4). Twenty-ve (24.5%) patients had intra-abdominal infection, 23 (22.5%) had pneumonia, and 17 (16.7%) had urinary tract infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal replacement therapy was performed in 55 patients (53.9%). The median (interquartile range) SOFA score was 11 (9)(10)(11)(12)(13)(14), the median (interquartile range) JAAM-DIC score was 6 (5-7), and the median (interquartile range) SIRS criterion was 3 (2-4). Twenty-ve (24.5%) patients had intra-abdominal infection, 23 (22.5%) had pneumonia, and 17 (16.7%) had urinary tract infection.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been pointed out that other metabolic processes, such as activated elastase-mediated degradation, might have a compensatory effect on the disappearance of TM alfa in patients with DIC and renal dysfunction [22,23]. Another study on a case of septic DIC with a TM alfa plasma concentration below 600 ng/mL reported that the decrease in the JAAM-DIC score from the baseline 4 days after TM alfa administration and the 90-day survival rate were signi cantly higher and lower, respectively [13]. Therefore, the TM alfa dosage in patients with severe renal dysfunction might be important in improving the prognosis of patients with septic DIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been pointed out that other metabolic processes, such as activated elastase-mediated degradation, might have a compensatory effect on the disappearance of TM alfa in patients with DIC and renal dysfunction [ 22 , 23 ]. Another study on a case of septic DIC with a TM alfa plasma concentration below 600 ng/mL reported that the decrease in the JAAM-DIC score from the baseline 4 days after TM alfa administration and the 90-day survival rate were significantly higher and lower, respectively [ 13 ]. Therefore, the TM alfa dosage in patients with severe renal dysfunction might be important in improving the prognosis of patients with septic DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effective blood concentration might not be reached at a dose of 0.02 mg/kg of TM alfa in patients with renal dysfunction. Imaura et al reported a significantly higher 90-day survival rate in patients with plasma levels of TM alfa higher than 600 ng/mL [ 13 ]. Therefore, reaching an effective TM alfa plasma concentration seems to be important for improving clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%